Letramentos múltiplos em (inter)ação: um estudo dos letramentos escolares desenvolvidos com alunos no final do ensino fundamental - Edna Maria Santana Magalhaes (2010)
The present research focus on practices of reading and writing and their relationship to eaching, learning and knowledge appropriation by elementary school students, and to act in multiple literacies contexts. Therefore, it may be seen as part of Literacy and Education Studies. The general objective of this research is to present, detail and analyze the concepts and practices adopted by the teachers of three different knowledge areas in a elementary school in Belo Horizonte, Brazil, relating them with the process of developing literacies skills an effective use of writing and reading in social interaction in various situations - from students on the final year of elementary school. The theoretical support is based upon theories focused on literacy(ies), orality, practices of reading and writing. On the linguistic researches area, the support will be provided by the contributions of Discourse Analysis, Interactional Sociolinguistics and Conversational Analysis. We consider too contributions of Literacies, Classes Interaction studies. All of these theoretical approaches have in common a conception of language, characterized as an activity in process, aiming the linguistic interaction among nterlocutors. Considering language by its discursive perspective presupposes the acceptance of different conditions of production that are present in and part of the verbal process of nteraction in various social contexts: subjects, places, goals and results of the dialogues held, imes and modes of their communication and interrelationships of subjects with other social contexts and these contexts together, practices and social practices within language. Some principles of Ethnography, in an interactional perspective, guided the collection of data during the research. Some targets shall be pointed: 1) the need to learn from the interaction between student/teacher, the concepts and practices of reading and writing of texts and materials which are used in the classroom; 2) the search for a methodological data processing hat could be related to linguistic theories that conceive language as interaction among subjects and, thus, 3) the possibility of analyzing teaching and learning processes held in the context of the classroom. As final considerations we present: a purpose to conceive the verbal nteraction in classroom understood as conversation because of its organization and the mood of students and teachers (inter)act with and by language(s); a taxonomy of questions, a brief reflection about teaching process focused on multiple literacies and, at the end, some perspectives to future researches.